A atuação de psicólogos escolares em Instituições de Ensino Superior do Triângulo Mineiro - Moura, Willian Araujo (2014)
Psychology has been establishing fruitful dialogues with Education, constituting in this fertile encounter the School Psychology, area of professional study, performance and development of psychologists. Among the educational contexts in which the School Psychology inserts itself, there is Higher Education, a field with incipient practices and productions by the school psychologist. In this sense, this research was aimed to investigate the performance of school psychologists in Higher Education Institutions (HEIs) in the Triângulo Mineiro region, Minas Gerais, Brazil. Thus, we made a survey of HEIs with classroom courses accredited by the Ministry of Culture, resulting in 33 institutions; among these, only four had school psychologists amid its employees at the time of research. After contact with these professionals, we conducted semi-structured interviews with two psychologists seeking to understand mainly how this performance and its constituent processes have been happening. We analyzed these interviews and built four categories based on Content Analysis that helps us think School Psychology in Higher Education, namely: (a) The concrete work conditions, (b) The relationships between theory and practice, (c) The processes of initial and continued professional development, (d) School Psychology in Higher Education as a performance context under work. The concrete determinations of the psychologists’ work such as extensive hourly work periods, high work demand, precarious physical space and the absence of other psychologists and of teamwork contributed to the understanding of the performed practices, urging us to go beyond appearances and immediacy, breaking with reductionistic views and actions still focused on the individual. Moreover, we found a speech segregating theory and practice, as well as a theoretical fragility, revealing the need for an epistemological consistency understanding and acting on and in reality. In this sense, it is essential to rethink the organization and its way of functioning of undergraduate Psychology, challenging curriculum and seeking to build actual critical possibilities for the initial and continued development of psychologists such as professional internships, supervisions, study groups, graduate programs, among others. Therefore, we found a performance still under development of School Psychology in Higher Education, so much so that the psychologists we interviewed presented practices yet far from institutional and collective actions, such as individual support to students with complaints in the teaching-learning process and interventions focused in the classroom, with virtually no work with families, educators and institutions’ employees. Despite the difficulties faced, that are many potentialities for the school psychologist’s performance in Higher Education; however, whatever the form of the psychologist’s performance in this context it should always be compromised ethically and politically with its historical and social reality, as well as the full development of the students, since Higher Education needs to be considered and performed as an effective development context of critically and socially committed citizens, beyond the mere technical sphere.